Unlocking the Secrets to Elevating Guest Satisfaction at Hotel Griya Persada Bandungan, Semarang Regency: A Sizzling Exploration of Service and Product Quality Analysis - Tuwuh Adhistyo Wijoyo; Guntur Suryaning H; Julian Andriani Putri (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This study, conducted at Hotel Griya Persada in Bandungan, Semarang, aimed to assess and describe methods for enhancing customer satisfaction by improving the quality of both products and services. The investigation specifically focused on physical evidence, reliability, responsiveness, assurance, and empathy within the service conditions. The findings revealed that there were certain areas of service quality that needed improvement, and some products did not meet customer expectations. Data for the study was collected through interviews and analyzed descriptively. The study involved eight participants, including one manager, two employees, and five consumers. The results were expected to provide valuable insights for management and customer satisfaction. Data analysis included techniques for data validation, reduction, data presentation, and drawing conclusions. The study indicated an improvement in both product and service quality for enhancing customer satisfaction. When it comes to product quality, eight key standards were identified, including flavor, consistency, texture, nutritional content, visual appeal, aromatic appeal, temperature, and recipes. Customers generally regarded the product quality at Hotel Griya Persada in Bandungan as good, but identified areas for improvement such as consistency, texture, temperature, and recipes. Regarding service quality, there were five elements within the five quality dimensions, namely reliability, responsiveness, assurance, empathy, and tangibility. Employees acknowledged the need for improvement in certain aspects, particularly in responsiveness and empathy, to enhance consumer satisfaction in future product purchases.